THE PRAGMATIC CHALLENGE OF SUSTAINABLE DEVELOPMENT - Renato J. Orsato, Renato (Revista Eletrônica de Administração, 2013)
There is a general acceptance amongst practitioners, academics and laypeople that the current fossil fuel basis of the energy industry is not ecologically sustainable. Future sources of energy must meet society’s needs and be environmentally benign. For energy companies, this represents the challenge of bridging the gap between today’s energy system and the vision of a sustainable future. Since the complete withdrawal from fossil fuels is not viable in the short term, what are the strategic choices available to energy firms? What factors influence their ability to integrate environmental prerogatives into corporate strategy and practices? In this article we address these questions by analyzing the organizational field of Shell Resources – a business unit of Shell Canada. In particular, we focus in two areas: investments in alternative energy and the greening of current production processes. We expect the work to be useful to both academics and managers dealing with environmental issues in business. Overall, the case provides an opportunity to reflect how a resource-intensive firm manages the dynamic between what is desirable and what is possible with respect to sustainable development.